5G and Satellite RF and Optical Integration - Varrall, Geoff (Artech, 2022)
5G and Satellite RF and Optical Integration, the latest ‘hot off the shelf’ groundbreaking book from Artech House authored by subject specialist Geoff Varrall is packed with essential time critical information. This updated edition has everything needed to know in order to understand the new world of terrestrial and non-terrestrial telecom technology. It analyzes the radio spectrum/band and technical specifications under consideration for 5G, along with the related performance, cost, and vertical market expectations. In addition, the book studies the cost of coexistence between 5G operators and other user communities' co-sharing spectrum, including GNSS; radio astronomers; radar; GSO, MEO, and LEO satellites in the Ku, K, and Ka bands and above; and satellite TV. Also covered is the role of free-space optical technology in 5G and satellite networks and what interference issues will arise from new band allocations. This includes co-shared allocations and how interference will be mitigated in and between next generation terrestrial and satellite 5G networks. The publication coincides with an inflection point where terrestrial, nonterrestrial, and RF and optical networks could be integrated in a financially useful way.